Development and Characterization of LDPE/Vermiculite Composites: Effects on Mechanical, Thermal, and Morphological Properties - Yesilyurt, Aysenur (Wiley-V C H Verlag Gmbh, 2025)
In this study, vermiculite (VMT), a naturally occurring layered silicate, was incorporated into a low-density polyethylene (LDPE) matrix at loading levels of 5 wt%, 7.5 wt%, 10 wt%, and 15 wt%. The composites were prepared by melt blending using a twin-screw extruder followed by injection molding. Thermal, mechanical, morphological and structural characterizations were conducted through thermogravimetric analysis (TGA), differential scanning calorimetry (DSC), tensile and flexural tests, Izod notched impact testing, scanning electron microscopy (SEM), and Fourier transform infrared spectroscopy (FTIR). TGA results indicated an increase in thermal degradation onset temperature from 357 degrees C (neat LDPE) to 389 degrees C (15 wt% VMT), confirming enhanced thermal stability. DSC analysis showed a slight reduction in crystallinity with increasing VMT content. The tensile and flexural moduli were improved proportionally with VMT loading, suggesting a stiffening effect, while elongation at break and impact resistance decreased, implying reduced ductility. SEM observations revealed good filler dispersion at low concentrations, but particle agglomeration and interfacial voids became evident at higher loadings. FTIR spectra confirmed the presence of VMT without any significant chemical interaction with the LDPE backbone. Overall, the incorporation of VMT enhances the rigidity and thermal resistance of LDPE composites, making them promising candidates for structural applications where dimensional stability and thermal performance are critical.
Keywords: inorganic fillers; LDPE; polymer matrix composites; vermiculite